An analysis of the female role in the social program Bolsa Família (Research, Society and Development, 2021)
This article aims to realize an analysis of the female role in the conditionalities imposed by the social program Bolsa Família. To achieve our purpose, we utilized a methodology of theoretical documentary analysis, which permits to contextualize and visualize our object of study. Firstly, we realized a brief historical background of the origin of the feminist movement and their fight for their rights (Pinto, 2010), then we did a panorama about the beginning of the programs of income transference in Brazil (Caus, 2015), and as well the appearing of the social program Bolsa Família (PBF) (Abreu, 2011). Posteriorly, we worked with questions which reflects the conditionalities and their negative influence on the beneficiaries’ lives, as also the inferiorization discourses which turn out to obligate the woman to handle with the imposed conditionalities by the social program (Gomes, 2011), consequently, we realized a debate between the positive and negative propositions that PBF provides by the income transference (Ferreira, 2012). As a result, our research points out that even the conditionalities redirect the women to a spot that they worked trough years and by means of movements to withdraw themselves, we affirmed that the beneficiaries can be considered as empowered women and, due to PBF, they can have autonomy and power of decision among their family.